Electrochemical reactivity of bulky-phenols with superoxide anion radical. (10th February 2019) - Zabik, Nicole L.; Anwar, Saba; Ziu, Iva; Martic-Milne, Sanela
Abstract: The 2, 6-di- tert -butyl-4-methylphenol (1 ), and its analogues 2, 6-di- tert -butylphenol (2 ), 2, 4, 6, -tri- tert -butylphenol (3 ), 2- tert -butylphenol (4 ), and 4- tert -butylphenol (5 ), were evaluated with respect to their reactivities with superoxide anion radical (O2 - ), using a variety of electrochemical methods including cyclic voltammetry and square wave voltammetry. The current intensity associated with anodic peak of O2 - oxidation into O2 (−1.16 ± 0.02 V) was used to measure effectiveness of compounds 1 –5 . All phenolic compounds reduced the anodic current intensity associated with O2 - oxidation into O2 . Compounds 2 and 4 produced reversible oxidation/reduction peaks associated with the corresponding quinones. The C10% and C60% values, related to the reduction of anodic O2 - /O2 current to 10% or 60% of its original value, were in 2.2–3.2 and 0.8–1.3 mM range, respectively. Compound 4 exhibited the lowest C10% and C60% values and was the most effective radical quencher. Data indicate that compounds belonging to the same class exhibited different radical activity (extent of reactivity with O2 - ), and that electrochemical methods are extremely useful in analyzing reactivity patterns in antioxidants of similar structures. Graphical abstract: Image 1